2016
DOI: 10.1097/cad.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAPK activation and mitochondrial cytochrome-c release in allicin-induced apoptosis in SK-N-SH cells

Abstract: Here, we investigate the apoptotic effect of allicin, the predominant component of freshly crushed garlic, on neuroblastoma cells. In this paper, the authors have first assessed the effect of allicin on human neuroblastoma SK-N-SH cells and then investigated the underlying mechanism. The results indicate that allicin suppresses SK-N-SH cell growth in a dose-dependent and time-dependent manner and that 5 μmol/l of allicin leads to a significant increase in apoptotic rate with annexin-V/PI double staining. Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Research has revealed that allicin targets multiple pathways implied in the inhibition of cancer development [27], including cell cycle arrest [21,28], the induction of apoptosis [29][30][31][32][33][34], the induction of histone acetylation [35] and the inhibition of angiogenesis [36]. Some of these studies dealing with the induction of apoptosis by allicin have also been reported for Caco-2 and HT-29 [20,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that allicin targets multiple pathways implied in the inhibition of cancer development [27], including cell cycle arrest [21,28], the induction of apoptosis [29][30][31][32][33][34], the induction of histone acetylation [35] and the inhibition of angiogenesis [36]. Some of these studies dealing with the induction of apoptosis by allicin have also been reported for Caco-2 and HT-29 [20,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Various cytotoxic agents induce apoptotic cell death via deactivation of MAPK signaling and induction of caspase-3 and -9 (31). In addition, the MAPK signaling pathway triggers the release of intermediate proteins in apoptosis, including cytochrome c, in cancer cells (32). Liu et al (33) reported that release of cytochrome c from the mitochondria was increased in the EF24-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of alterations in JNK and p38 MAPK pathways in NB cell growth has been investigated less. Higher sensitivity to apoptotic stimuli has mainly been reported in NB cell lines upon pharmacological inhibition of JNKs or p38s, although an anti-apoptotic outcome after inhibition of these MAPKs has also been reported [55,56,57,58,59] (Table 1). A complex scenario emerges in NB in which the specific contribution of the effectors from the distinct MAPK pathways may differentially drive NB cell growth, differentiation, and apoptosis, with variable consequences in the response to chemotherapies.…”
Section: Neuroblastoma Cell Growth and Differentiationmentioning
confidence: 99%